Implementation of the Share, Think, Observe, and Present (STOP) Model in Cooperative Learning to Improve Understanding of Islamic Religious Education for Elementary School Students - Mita Hasi (Jurnal Indonesia Pendidikan Profesi Guru, 2025)
Background: Group discussion skills are essential for promoting collaboration and active student engagement in Islamic Religious Education (PAI); however, elementary school students often struggle to participate actively, particularly when worship-related materials are taught using conventional methods. Objective: This study aimed to improve the group discussion skills of fourth-grade students at SD Negeri 96 Kaur through the implementation of the Share, Think, Observe, and Present (STOP) cooperative learning model in PAI, with a focus on worship-related content. Method: This study employed Classroom Action Research (CAR) consisting of two cycles, each comprising the stages of planning, implementation, observation, and reflection. The participants were 30 fourth-grade students. Data were collected through observation sheets, learning achievement tests, interviews, and documentation and were analyzed descriptively. Results: The findings revealed a significant improvement in students’ group discussion skills. The percentage of students who met the Minimum Competency Standards (KKM) increased from 36% in the pre-cycle to 64% in Cycle I and reached 86% in Cycle II. Conclusion: The STOP model proved effective in enhancing students’ group discussion skills and promoting active participation in PAI learning. Contribution: This study contributes to the development of practical, student-centered learning strategies for improving collaborative skills in elementary-level Islamic Religious Education.